Minimally invasive plate osteosynthesis of distal tibial fracture using a posterolateral approach: A cadaveric study and preliminary report - Apipop Kritsaneephaiboon (2018)
Purpose: The aims of this anatomical study were to evaluate the feasibility of minimally invasive plate osteosynthesis (MIPO) using a posterolateral approach in distal tibial fractures and to study the relationship between neurovascular structures and the plate. Methods: Two separate incisions, one proximal and one distal, were made on the posterolateral aspect of ten cadaveric legs in the prone position. A 14-hole contralateral anterolateral distal tibial locking plate was inserted into the submuscular tunnel using a posterolateral approach, and one screw was fixed on each side of the proximal and distal tibia. The MIPO tunnel was then explored to identify the relationship between neurovascular bundles and plate. Results: For the proximal incision, retraction of the flexor hallucis longus and the tibialis posterior muscles medially was very important because it could protect the posterior tibial artery and the tibial nerve during plating. The sural nerve and lesser saphenous vein were easily identified and retracted in the superficial layer of the distal incision. In addition, we achieved satisfactory outcomes after using this MIPO technique in one patient. Conclusion: Based on the results of our study, it seems that using the MIPO technique through a posterolateral approach should be a reasonable and safe treatment option for distal tibial fractures, especially when the anterior soft tissue is compromised. However, studies with a higher level of evidence should be done in more patients to confirm the clinical safety of using this technique. © 2012 Springer-Verlag Berlin Heidelberg.